Selectivity and residual weed control of pre-emergent herbicides in soybean crop1 - Gazola, Tiago [UNESP]; Gomes, Diego Munhoz; Belapart, Diego [UNESP]; Dias, Márcio Furriela [UNESP]; Carbonari, Caio Antonio [UNESP]; Velini, Edivaldo Domingues [UNESP] (Universidade Federal de Viçosa, 2021)
The use of pre-emergent herbicides is important for the current agricultural production systems that present weeds resistant to herbicides. Considering the complexity of using these products, the objective of this work was to evaluate their selectivity and residual weed control in soybean crops and their effect on the weeds Amaranthus hybridus, Bidens pilosa, Digitaria insularis, Eleusine indica, and Euphorbia heterophylla. The herbicide selectivity experiments were conducted under field conditions in the 2017/18 and 2019/20 crop seasons and the herbicide efficacy experiments were conducted under greenhouse conditions. The herbicides s-metolachlor and flumioxazin can be applied on day of the soybean sowing without causing significant grain yield losses. Diclosulam and sulfentrazone are safe for soybean crops when applied at least 14 days before sowing. The herbicides used proved to be good options for weed management systems for soybean crops; flumioxazin and sulfentrazone were the herbicides that promoted the best control for all evaluated weed species and ensured a residual effect of at least 30 days.
Keywords: Diclosulam; flumioxazin; Glycine max; s-metolachlor; sulfentrazone; weeds